Artifical Intelliegnce (AI) Ethics Meets Ubuntu: Towards A Context-Aware Governance Model For Sustainable Innovation In Africa - Mutswiri, Prosper; Hapanyengwi, Gilford T; Chipfumbu, Colleta T (International Journal of Scientific Research and Management (IJSRM), 2025)
Artificial intelligence (AI) is rapidly diffusing across African societies, yet most governing frameworks arrive as de-contextualised imports that privilege individual autonomy and post-hoc liability. Drawing on Ubuntu, an indigenous relational philosophy that defines personhood through reciprocal obligation, this paper conducts a systematic review (2018 April 2025) of peer-reviewed and grey scholarship on Ubuntu-centred AI ethics. Thirty three eligible studies are interrogated through a pluralistic lens that couples Ubuntu ethics with relational autonomy theory and socio-technical systems analysis. Nine recurrent themes are identified, including communal data stewardship, collective responsibility, and contextual conceptions of fairness, ecological sustainability and intersectionality. While Ubuntu offers a powerful counter-narrative to data colonialism and responsibility gaps, empirical evidence of its operationalisation remains sparse and uneven. To translate ethos into practice, the article proposes a five-layer governance architecture including (1) Community Data Trusts, (2) Relational Design Praxis, (3) Harm Reconciliation Panels with risk-bond funding, (4) Ecological Stewardship Protocols, and (5) Developer Benefit Realisation. This modular model embeds Ubuntu values across the AI life-cycle while remaining compatible with statutory regimes and technical constraints. The study concludes that Ubuntu-aligned governance can enhance trust, equity and sustainability in African AI deployments, but realisation depends on sustained capacity-building, intersectional safeguards and iterative empirical evaluation.